Does Adiponectin Act as an Antiangiogenic Factor in B-Cell Chronic Lymphocytic Leukemia? - Stefano Molica; Giovanna Digiesi; Angelo Vacca; Rosanna Mirabelli; Katia Todoerti; Caterina Battaglia; Fortunato Morabito; Antonino Neri; Domenico Ribatti (Advances in Hematology)
Angiogenesis is involved in the pathogenesis of B-cell chronic lymphocytic leukemia (CLL), and high microvascular density has been found in CLL to be associated with a poor prognosis. In this study, we assessed serum levels of adiponectin in 69 patients with Binet stage A B-CLL, and these values were retrospectively correlated with bone marrow (BM) microvessel area and serum levels of vascular endothelial growth factor (VEGF), fibroblast growth factor-2 (FGF-2), angiogenin, PECAM-1 (CD31), matrix metalloproteinase-9 (MMP-9), interleukin-8 (IL-8), syndecan-1, and the percentage of CD38+ or ZAP-70+ CLL cells. The positive correlation between serum levels of adiponectin and VEGF (P=.03) does not translate into an increase of the extent of BM angiogenesis (P=.404), FGF-2 (P=.348), angiogenin (P=.402), and CD31 (P=.248) serum concentrations. Accordingly, IL-8 (P=.175), syndecan-1 (P=.06), and MMP-9 (P=.144) circulating levels were not likely to reflect adiponectin concentration. Furthermore, patients with higher levels of adiponectin had a more favorable biological profile as defined by a lower number of both CD38− (r=−0.294; P=.02) and ZAP-70+ (r=−0.285; P=.04). Finally, we evaluated the presence of adiponectin in B-CLL cells at gene expression level. RMA intensity values for adiponectin gene transcript denote a homogeneous low expression in B-CLL cells, whereas VEGF transcript was highly expressed with a degree of interpatient variability. Overall, these data seem to indicate that adiponectin could be involved as an antiangiogenic factor in B-CLL.